Clinical optimization of bexmarilimab as a myeloid checkpoint therapy - Karthikeyan, Mahalakshmi; Mickos, Jesper; Hollmén, Maija (Informa UK Limited, 2026)
Checkpoint blockade has revolutionized cancer therapy, yet durable responses are limited by myeloid-driven immunosuppression. Bexmarilimab, a first-in-class monoclonal antibody targeting the scavenger receptor Clever-1 (Stabilin-1), represents a novel strategy to recondition tumor-associated macrophages and malignant myeloid cells. This review summarizes the biological rationale for Clever-1 targeting, appraises clinical and translational evidence, and outlines strategies to enhance therapeutic efficacy through patient selection, rational drug combinations, biomarker-driven patient stratification, and timing of intervention. We also highlight future opportunities for integrating bexmarilimab with next-generation immunotherapies and precision medicine approaches.